Application of multi-seismic attributes analysis in the study of distributary channels. (August 2016) - Li, Xutao; Chen, Qilin; Wu, Chaodong; Liu, Huaqing; Fang, Yanan
Abstract: During the exploration of stratigraphic reservoirs, the key to locating these reservoirs is to identify the sandstone distribution. Seismic data can be used to recognize large-scale distributary-channel sedimentary bodies; however, depiction of sedimentary bodies in small distributary channels using traditional interpretation data from seismic profiles is extremely difficult. In the Upper Cretaceous first sandstone bed of the third member of the Nenjiang Formation (called the Nen 3 member for simplicity) in the XB area of the southern Songliao basin, distributary channels are the main sedimentary facies. The distributary channels migrate frequently; therefore, it is difficult to precisely depict the morphology of the channel and the distribution of sandstone. In this study, we investigated the deposition of distributary channels using equal-scale formation plane seismic attributes such as post-stack amplitude, instantaneous amplitude and seismic waveform classification, analyzed well logging data from target formations, and mapped the distribution of distributary channels. This study shows that seismic sedimentological study and stacking multiple attribute analysis can identify the distribution of distributary channels precisely and effectively. The attributes of equal-scale strata slices are evidently superior to those of time and horizon slices; Attribute extraction and selection of equal-scale formation slices is an essential step. The comprehensive selection of seismic attributes that show a good correlation to a single-well can be used to clearly depict channel bodies. The overlap of the 40-Hz single-frequency energy and the RMS amplitude depicts the sedimentary characteristics and shapes of sandstone bodies in main channels as well as small-scale distributary channels more clearly than a single attribute. These attributes show that the first sandstone bed of the Nen 3 member was from distributary channels with complex shapes. The distributary channels cut across each other vertically and laterally. It indicates that, during the deposition of the Nen 3 member in XB area, the direction of the main channel is from north to south, and the provenance could be from north and east. The method of this paper may provide some helpful suggestions to the geologist using seismic attributes to undertake research on sedimentary environment at other places in the world. Highlights: The attributes of equal-scale strata slices are evidently superior to time and horizon slices. The overlap of the 40-Hz single-frequency and the RMS amplitude depicts the shapes of distributary channels clearly. The direction of the distributary channel of Nen 3 member in XB area is from north to south.